Children Preoperative Anxiety Levels at Operating Room of Brayat Minulya Hospital, Surakarta - Widodo, Widodo; Yulianti, Natalia Ratna; Gayatina, Andri Kenti (Infomasi dan Promosi Kesehatan, 2024)
Introduction: Preoperative is the initial stage of perioperative care which begins when the patient enters the reception room and ends when the patient is transferred to the operating table for surgery. At this stage, most people who undergo it will feel anxious, including pediatric patients. Pediatric patients often exhibit preoperative anxiety that influences intra- and postoperative nursing care. Mapping preoperative children's anxiety levels as a basis for determining preoperative treatment strategies for pediatric patients in the IBS Hospital reception room. Brayat Minulya needs to be done. Purpose: This study aims to identify the preoperative anxiety level of school-aged children in hospitals. Brayat Minulya Surakarta. Method: This research design is a descriptive study with a survey approach. Data collection was carried out using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Sampling used total sampling with a sample size of 62 respondents who had adjusted to the inclusion and exclusion criteria. Data were analyzed using quantitative descriptive analysis methods. Results: Description of anxiety in preoperative school age children with no anxiety as many as 5 respondents (8.06%), mild anxiety as many as 21 respondents (33.87%), moderate anxiety as many as 27 respondents (43.55%), severe anxiety as many as 9 respondents (14.52%), and no respondents had very severe anxiety/panic. Conclusion: The number of children with moderate levels of anxiety is the largest, namely 43.55%. Future research can measure the relationship between gender and surgical experience with children's preoperative anxiety levels and use the gold standard, the State-Trait Anxiety Inventory for Children (STAIC) to measure children's anxiety levels.